RADEC Model on Critical Thinking Skills of Science Education In Elementary School: A Systematic Literature Review - Reza Pahlevi (GENFABET: Generasi Pendidikan Dasar, 2025)
This study employs a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol to evaluate the effectiveness of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model in enhancing critical thinking skills among elementary school students. A total of 21 peer-reviewed studies published between 2019 and 2025 were analyzed. The findings show that the RADEC model enhances critical thinking, particularly in science education. Through its structured stages, the model promotes active engagement, social interaction, reflective thinking, and conceptual understanding. Despite these benefits, challenges such as low student literacy, limited teacher readiness, and insufficient institutional support were identified. These results highlight the need for comprehensive teacher training and institutional support to ensure successful implementation. The RADEC model presents itself as a promising and adaptable approach for promoting 21st-century competencies in primary education.